PERAN LEMBAGA PENDIDIKAN TINGGI KEOLAHRAGAAN DALAM MENGATASI KETERLANTARAN PENDIDIKAN JASMANI DI SD - ., Dimyati (Jurnal Cakrawala Pendidikan, 2005)
A study ofvarious literature reveals that well-held physical education at elementary school can guarantee the growth of physical and moral quality in the child. But in reality the implementa tion ofphysical education at elementary school has been confronted with various problems ranging from inadequate equipment and facilities and limited time allocations and to low-quality teachers. The continuing occurrence ofthese various constraints has caused physical education at elementary school to experience a condition of neglect at levels ranging from a pedagogic one to a philosophical one. Such a reality ofthe neglect ofphysical education as mentioned above represents a crisis entangling various factors in its roots. There fore, any effort to overcome it must be done by means Ofa synergism among and involving various concerned parties in the reconstruction ofphysical education at elementary school. Higher educational insti tutions ofsports hold a vital role in drawing up and bringing about quality physical education at various levels ranging from the nursery school to college. This strategic r.ole obliges them to have a vision capable to accomodate the expanding demands ofsociety, including in it howthat vital role can be actualized in overcoming the weakening pedagogic level ofphysical education teachers at elementary school. This article will analyze and lay open the role that ought to be conducted by higher educational institutions ofsports. Key words: neglect, physical education, elementary school, higher education in sports